Sentiment Analysis of Customer Satisfaction with the Services of the Waikelo Port Class III Administrative Office Using the CAN Order Method - Kamalia Ahmad; Friden Elefri Neno; Alexander Adis (Journal of Computing Innovations and Emerging Technologies, 2026)
This study aims to analyze customer satisfaction levels with the services provided by the Waikelo Port Class III Administrative Office using the CAN (Cumulative Agreement Normalized) Order method and sentiment analysis. Data was collected from customer comments on service aspects such as speed of service, staff friendliness, facilities, and registration procedures. The comments were processed through text pre-processing, including case folding, tokenization, stopword removal, and stemming, then analyzed using the VADER Sentiment Analyzer to obtain positive, neutral, and negative scores. These sentiment values were used as input to calculate the CAN value, which determines the satisfaction ranking of each alternative objectively. The results show that service alternatives focusing on speed and staff friendliness have the highest CAN value of 0.83, while alternatives related to facilities and queues have the lowest CAN value of 0.33, indicating aspects that need improvement. Evaluation of the consistency of the CAN ranking with the respondent ranking using Spearman Rank Correlation yields a value of 0.92, indicating a high degree of conformity between the CAN method and customer preferences. This analysis proves that the integration of sentiment analysis and the CAN Order method can provide a quantitative picture of customer satisfaction levels and serve as a basis for practical recommendations to improve service quality.